Posterior Nasal Neurectomy in Allergic Rhinitis - Bobby Setiawan; Dolly Irfandy (Majalah Kedokteran Andalas, 2022)
AbstractIntroduction: Allergic rhinitis is an immunological response mediated by IgE from the nasal mucosa which is characterized by clear discharge from the nose, nasal congestion, itching of the nose. Endoscopic sinus surgery is performed in cases of allergic rhinitis that have comorbid factors such as chronic rhinosinusitis and nasal polyps. Therapy for rhinitis allergy including anti histamine, intranasal corticosteroid and immunotherapy. Surgical techniques such as selective posterior nasal neurectomy can be performed in patients with severe allergic rhinitis.  Rhinosinusitis is based on sinonasal symptoms and inflammation of the sinonasal mucosa. Case Report: We report a case of a 20-year-old female patient who was diagnosed with chronic rhinosinusitis and allergic rhinitis which was managed by Functional Endoscopic Sinus Surgery (BSEF) and posterior nasal neurectomy. Conclusion: Posterior nasal neurectomy is one of the surgical procedures that can be performed on patients with allergic rhinitis who do not improve with treatment.